Empowerment of Fishers Groups: Cooperation Activation of Capacity Building Programs for Family Heads In Bondo Beach Coast, Jepara Regency - Ahmad Kharis (Journal of Nahdlatul Ulama Studies, 2020)
This article aims to explain fishers groups' strategy in facing the dry or western season in Bondo Village, Jepara Regency. For a month, the fishers do not go to sea because of the danger of big waves. Thus forcing the adaptation of the marine economic cycle to land or experiencing job subversion. On the other hand, the Covid-19 pandemic has increasingly suppressed community activities to limit themselves from leaving the house and comply with health protocols. If this condition is left without collaborative efforts by actors, it will create new low groups. Of course, this condition is not desired by all people, so cross-stakeholder collaboration is needed. The role of multi-stakeholders is crucial in supplying socio-economic flows that positively impact lifting the welfare minus group to empowerment. This article will discuss the strategies adopted by fishers groups to survive during the dry season accompanied by civil society opportunities to work, namely the Nahdlatul Ulama Sub-Branch to help prosper the community Bondo Village, Jepara Regency.